Seed development and seed shedding in North Italian ecotypes of Lolium multiflorum - Raja Harun, Raja Muhammad; Bean, E. W. (Blackwell Scientific Publications, 1979)
Seed development and seed shedding were studied in seven populations of Lolium multiflorum. Five of these populations were from the North Italian Plains, two from the Piedmont area and three from the Lombardy region. The remaining populations were Delecta, a variety derived from ecotypes from the Lombardy Plain, and RvP Lemtal. Seed shedding was greatest in the three ecotypes from the Lombardy Plain and lowest in RvP Lemtal. The two ecotypes from the Piedmont Plain, and Delecta, gave intermediate values. Moisture loss during ripening was greatest in the Lombardy ecotypes but there were no differences in the time taken to reach maximum 1000-seed weight. Germination values had reached a maximum 27 d after anthesis in all populations. It is suggested that the North Italian ecotypes, or varieties derived from them, should be harvested by direct combining at a moisture concentration of 450 g kg-1 (≡45%) to obtain the maximum weight of germinable seed.